Clinical outcomes of anterior prostate cancers treated with robotic assisted radical prostatectomy. Issue 3 (27th October 2022) - Saghir, Reyan; Russell, Beth; Kum, Francesca; Darwish, Raef; Deane, Jude; Allen, Christopher; Rizwi, Hira; Saghir, Noman; Mayor, Nikhil; Cathcart, Paul; Dasgupta, Prokar; Popert, Rick; et al.
Abstract: Introduction: A prospective cohort study comparing peri‐ and postoperative outcomes for patients with predominantly anterior prostate cancer (APC) identified preoperatively against non‐anterior prostate cancer (NAPC) treated via robotic‐assisted radical prostatectomy (RARP). Patients and Methods: Of the 757 RARP's completed between January 2016 and April 2018, two comparative cohorts for anterior and an equivalent group of non‐anterior prostate tumours each consisting of 152 patients were compared against each other. Data were collected on the following variables: patient age; operating consultant; preoperative PSA, ISUP grade, degree of nerve sparing; tumour staging; presence and location of positive surgical margins; PSA density, postoperative ISUP grade; treatment paradigm and postoperative PSA, erectile function, and continence outcomes with 2‐year follow‐up. Results: APCs were found to have significantly lower ISUP grading postoperatively; increased diagnosis via active surveillance over new diagnosis; more frequently undertaken bilateral nerve‐sparing and long‐term poorer continence outcomes at 18 and 24 months postoperatively ( p < 0.05). Pre‐ and post‐op PSA levels, erectile function, PSA density, positive surgical margins (PSM), age and tumour staging showed no significant differences between the APC and NAPC cohorts ( p > 0.05). Conclusion: The lower ISUP grading could indicate APC as overall being less aggressive than NAPC, whereas the poorer long‐term continence outcomes require further investigating. The non‐significant differences amongst tumour staging, PSA density, preoperative PSA levels and PSM rates suggest that APC may not be as significant as predicted in diagnostic evaluation. Overall, this study provides useful information on the growing literature of anterior prostate cancer. Being the largest comparative cohort study to date on APC post‐RARP, these results indicate the true characteristics of anterior tumours and their functional outcomes to help improve education, patient expectations and management.